Effect of Anaerobic Soil Disinfestation and Mustard Seed Meal for Control of Charcoal Rot in California Strawberries. (30th November 2016) - Muramoto, Joji; Shennan, Carol; Zavatta, Margherita; Baird, Graeme; Toyama, Lucinda; Mazzola, Mark
ABSTRACT: Anaerobic soil disinfestation (ASD) and mustard seed meal (MSM) appear to be promising non-fumigant alternatives for soilborne pathogens control. However, studies of their effect on charcoal rot caused by Macrophomina phaseolina in California strawberry are limited. A demonstration field trial with ASD with rice bran 20 t ha –1 (ASD-RB), MSM 4.5 t ha –1 (MSM), and ASD with rice bran 6.7 t ha –1 + MSM 4.5 t ha –1 (ASD-RB+MSM) treatments was conducted in a M. phaseolina -infested organic field in Oxnard, CA. A doubling of fruit yields relative to the grower standard, and a reduction in plant mortality by M. phaseolina, was achieved by ASD-RB. MSM failed to control M. phaseolina and resulted in fruit yields that were more than 20% below the ASD-RB yield. Fruit yield in the ASD-RB+MSM plot was intermediate between ASD-RB and MSM. Treatment effects on soil pH, EC, inorganic N dynamics, and soil microbial communities were also examined.